Analisis Yuridis Perlindungan Hukum terhadap Korban Pembelian Emas Curian dengan Itikat Baik - Semy B.A Latunussa; Yulianus Pabassing; Nurhasanah (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze legal protection for victims who purchase stolen gold in good faith and to identify obstacles in its implementation. The research method used is empirical juridical research with a normative juridical approach through the study of legal regulations, legal theories, and practices in society. The results indicate that buyers who are unaware of the origin of the gold and conduct transactions fairly are entitled to legal protection as good-faith parties. However, such protection faces obstacles, including gold trading practices without ownership documents, difficulties in proving good faith, and the risk of being charged with the criminal offense of receiving stolen goods.